"Frequency of Glutathione S-transferase M1 (GSTM1) and GSTT1 Null Genotypes in Fars Population (South of Iran)" - M Saadat; DD Farhud; I Saadat (Iranian Journal of Public Health, 2001)
The genes glutathione S-transferase M1 (GSTM1) and GSTT1 code for cytosolic enzymes GSTµ and GSTθ, respectively, which are involved in phase II metabolism. In human, both genes may be deleted. In the present study, the genetic polymorphisms of GSTM1 and GSTT1 were detected by PCR method in 236 healthy individuals from Shiraz population, Fars province, south of Iran. The frequency of GSTM1 and GSTT1-null genotypes were 37.7 and 31.8 percent, respectively. The studied population was then compared with reported frequencies for neighboring populations, as well as, with those for European and African populations.